The relationship between general upper-body strength and pole force measurements, and their predictive power regarding double poling sprint performance - Mende, E.; Schwirtz, A.; Paternoster, F. K. (Journal of Sports Science & Medicine, 2019)
In recent years, there is an increasing importance of double poling (DP) performance regarding the outcome in classic cross-country skiing (XCS) races. So far, different approaches were used to predict DP performance but there is a lack of knowledge how general strength parameters are related to DP performance parameters gathered from in field-test situations. Therefore, the aim of this study was to determine the relationship between general strength measurements of different upper-body segments and pole force measurements during a DP sprint exercise. In addition, multiple linear regressions were calculated to determine the predictive power of theses variables regarding DP sprint performance, represented as maximum velocity. Thirteen none-elite cross-country skiers performed two 60 m DP sprints at maximal speed on a tartan track using roller skis. In addition, maximum isometric and concentric strength tests were performed on a motor-driven dynamometer with four major upper-body segments (trunk flexion / extension, shoulder / elbow extension). Especially the mean pole force and the strength test parameters correlated significantly (r = 0.615) in all except one comparison. However, regression analyses revealed that neither pole force parameters (R² = 0.495) nor isometric (R² = 0.456) or dynamic (R² = 0.596) strength test parameters could predict the DP performance significantly. This study showed that standardized isokinetic strength tests could be used to estimate pole force capabilities of XCS athletes. However, pole-force and strength test parameters failed to predict significantly maximal velocity during a DP sprint exercise, which might be attributed to the non-elite subject group. Key Points